2010
DOI: 10.1111/j.1365-2672.2010.04752.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of Escherichia coli in waters using fluorescent in situ hybridization, direct viable counting and solid phase cytometry

Abstract: Aims:  We developed an improved Fluorescent In Situ Hybridization FISH‐based method to detect viable Escherichia coli cells by solid phase cytometry (SPC), and results were compared to those obtained by the standard culture method. Methods and Results:  The method includes a direct viable count (DVC) assay, multi‐probes labelled and unlabelled (helpers) to detect specifically viable E. coli cells and to enhance SPC cell counts. We demonstrate that helpers increase the fluorescence intensity of hybridized E. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 41 publications
0
24
0
1
Order By: Relevance
“…It has been shown that this tyramide signal amplification results in an up-to-20-fold increase of the signal from that of normal FISH (22,33). Solid-phase cytometry has already been successfully applied for the quantification of bacterial populations occurring at low concentrations in drinking water (23), for Legionella pneumophila (4), and for fecal indicator organisms like Escherichia coli (6).…”
mentioning
confidence: 99%
“…It has been shown that this tyramide signal amplification results in an up-to-20-fold increase of the signal from that of normal FISH (22,33). Solid-phase cytometry has already been successfully applied for the quantification of bacterial populations occurring at low concentrations in drinking water (23), for Legionella pneumophila (4), and for fecal indicator organisms like Escherichia coli (6).…”
mentioning
confidence: 99%
“…Viable staining with fluorescent dyes is effective to reduce such false signals because only living cells can be marked. In fact, fluorescent viable staining has been successfully applied to micro-colony methods (Wang et al, 2007), as well as to rapid methods based on the direct detection of single cells (Matsuoka et al, 2003;Baudart and Lebaron, 2010;DeJong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cholera, typhoid fever, bacillary dysentery, leptospirosis and gastroenteriris are some examples of waterborne diseases caused by Vibrio cholera, Salmonella typhi, Shigella spp., Leptospira spp., and Enteropathogenic Escherichia coli [EPEC] (Ashbolt, 2004). Table 1 resumes the latest screening methods for waterborne bacteria; capture and detection methods, limit of detection [LOD] and range of detection are compared (Baudart & Lebaron, 2010;Bharadwaj et al, 2011;Bruno et al, 2010;Chen et al, 2008;Duplan et al, 2011;Fu et al, 2010;Geng et al, 2011;Guven et al, 2011;Huang et al, 2008Huang et al, , 2011Karsunke et al, 2009;Kwon et al, 2010;Li et al, 2011A;Luo et al, 2010;Miranda-Castro et al, 2009;Park et al 2008;Sun et al, 2009;Wilbeboer et al, 2010;Wolter et al, 2008;Yoon et al, 2009;Yu et al, 2009;Xue et al, 2009). …”
Section: Bacteria Biosensorsmentioning
confidence: 99%
“…Besides, these methods are costly and time consuming. Because of its great importance as faecal contaminant indicator in waters, the development of biosensors to detect and quantify E. coli has been extensively studied and there are a very large number of new methods and improvements to reference methods (Choi et al, 2007;Deobagkar et al, 2005;Gau et al, 2001;Yáñez et al, 2006;Liu & Li, 2002;Simpson & Lim 2005;Tang et al, 2006;Yoo et al, 2007;Yu et al, 2009 The immunological methods are the most widely used as recognition methods (Bharadwaj et al, 2011;Duplan et al, 2001;Fu et al, 2010;Guven et al, 2011;Huang et al, 2011;Karsunke et al, 2009;Know et al, 2010;Luo et al, 2010;Park et al, 2008;Wolter et al, 2008;Yoon et al, 2009;Yu et al 2009), but nucleic acid capture probe are starting to gain some (Baudart & Lebaron, 2010;Bruno et al, 2010;Chen et al, 2008;Geng et al, 2011;Li et al, 2011;Sun et al, 2009;). The use of aptamers instead of antibodies [Abs] as capture probes are increasing due to the advantages they present against Abs.…”
Section: Bacteria Biosensorsmentioning
confidence: 99%